2016
DOI: 10.15740/has/eti/7.1/1-7
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of welded joints using friction stir welding, metal inert gas and tungsten inert gas

Abstract: In this paper, a comprehensive practical study in mechanical properties and cost welding of welded Aluminum 6061 pipe using three different types of welds, Metal Inert Gas (MIG), Tungsten Inert Gas (TIG) and Friction Stir Welding (FSW) with rotation speed (1800 RPM) and travel speed 4mm/min. The mechanical properties of the weld have been also investigated using the hardness, elongation and tensile tests. The microstructure of the welds, including the nugget zone and heat affected zone, has been compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…From the analysis, it was concludedthat due to the presence of various alloying elements and post weld heat treatments the tensile strength and ductility of the base metal is significantly higher than the weld bead. Khoushid AM et al (Khourshid AM 2016) studied the mechanical properties of welded aluminum 6061pipe using three different types of welds.Weldments with rotation speed (1800 RPM) and travel speed 4mm/min of MIG, TIG and Friction welding were compared. The microstructure of the welds, including the nugget zone and heat affected zone, has been compared and concluded that the microhardness values are higher in the weld region of FSW joints compared to MIG and TIG.…”
Section: Introductionmentioning
confidence: 99%
“…From the analysis, it was concludedthat due to the presence of various alloying elements and post weld heat treatments the tensile strength and ductility of the base metal is significantly higher than the weld bead. Khoushid AM et al (Khourshid AM 2016) studied the mechanical properties of welded aluminum 6061pipe using three different types of welds.Weldments with rotation speed (1800 RPM) and travel speed 4mm/min of MIG, TIG and Friction welding were compared. The microstructure of the welds, including the nugget zone and heat affected zone, has been compared and concluded that the microhardness values are higher in the weld region of FSW joints compared to MIG and TIG.…”
Section: Introductionmentioning
confidence: 99%
“…A tool pin diameter of 5 mm, a tool rotational speed of 1800 rpm, and welding speed of 10 mm/min were found to be the optimal process parameters. Khoushrid et al [123] employed regression analysis to optimize the process parameters for joining aluminium alloy 6061 pipes using the FSW process. Te regression equations, which were the results of their investigation, are as follows:…”
Section: Employment Of Optimizationmentioning
confidence: 99%
“…J. tusek with his colleagues [11] welded long L sections of steel by submerged arc welding with single, twin and triple wire and concluded that costs for welding with single wire was 20 % and 30 % higher than twin and triple-wire electrode respectively. Friction stir welding is cost effective for larger annual production; however, metal inter gas and tungsten inert gas for small-volume production in case of pipes welding [12]. The previous research has shown that the microdefects exist in the joints and leads to failure during service.…”
Section: Introductionmentioning
confidence: 99%